Rescuing impairment of long-term potentiation in fyn-deficient mice by introducing Fyn transgene - Kojima, Nobuhiko (The National Academy of Sciences of the USA, 1997)
To examine the physiological role of the Fyn tyrosine kinase in neurons, we generated transgenic mice that expressed a fyn cDNA under the control of the calcium/calmodulin-dependent protein kinase IIα promoter. With this promoter, we detected only low expression of Fyn in the neonatal brain. In contrast, there was strong expression of the fyn-transgene in neurons of the adult forebrain. To determine whether the impairment of long-term potentiation (LTP) observed in adult fyn-deficient mice was caused directly by the lack of Fyn in adult hippocampal neurons or indirectly by an impairment in neuronal development, we generated fyn-rescue mice by introducing the wild-type fyn-transgene into mice carrying a targeted deletion in the endogenous fyn gene. In fyn-rescue mice, Schaffer collateral LTP was restored, even though the morphological abnormalities characteristic of fyn-deficient mice were still present. These results suggest that Fyn contributes, at least in part, to the molecular mechanisms of LTP induction.